The Concept of Management Accounting in Crisis Conditions - BOBRYSHEV, Aleksey Nikolaevich; YAKOVENKO, Viktor Sergeevich; TUNIN, Sergey Aleksandrovich; GERMANOVA, Victoria Samvelovna; GLUSHKO, Anatoly Yakovlevich (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
The modern theory of accounting management does not fully explain the mechanisms of decision-making in conditions of non-standard behavior of economic agents, such as periods of hyperinflation, and distinct manifestations of stagnation and depressive phenomena in the economy. Regarding this, the article aims to reveal the theoretical basis of the formulation of the accounting management system in crisis conditions. Modern theory of accounting management is focused on the diagnosis of the internal environment for making management decisions, while negative factors of the external environment are beyond the scope of accounting and analysis. This makes it impossible to assess the impact of inflation, exchange rate fluctuations, volatility in the stock markets, depressive factors in the individual sectors of the economy, etc. This requires conceptual and theoretical justification techtologycal boundaries of the allocated subsystem in the context of interaction with the higher level system, the formation of structural components allocated to subsystems (functions, principles, objects, tasks), identify areas of improvement tools generated subsystem. The individual components of the concept of formation of anti-crisis subsystem of accounting management were formulated by the authors for the first time. Also, questions of regularities of development of accounting management and drawbacks of its methodology were concerned in the works of leading Russian scientists who are working in the field of development of accounting management. In this article the authors formulated their own point of view on a number of such controversial questions that represents a new vector for further adaptation of tools of management accounting to the realities of the domestic economy, as well as cyclic processes affecting it.